Nedenunțarea infracțiunii: concept, forme, studiu comparat [Articol] - Copeţchi, Stanislav (CEP USM, 2022)
In the present study is analyzed failure to report a crime as a form of involvement in the crime. The features of failure to report a crime are identified. The similarities and differences between failure to report a crime and criminal participation are established. It is noted that the national legal framework does not contain regulations on failure to report a crime. At the same time, it is noted that in the legislation of some foreign states (much more civilized) the failure to report a certain category of crimes constitutes an offence. It is concluded that the Moldovan legislator should also criminalize such conduct. In this regard, is proposed an incriminating way to penalize a failure to report offenses of a certain gravity.
Keywords: failure to report a crime; participation; involvement in the crime; comparative study